LEGALITY OF MULTIPLE POSITIONS OF VICE CHAIRMAN OF THE COUNCIL OF INDRAMAYU REGENCY BASED ON THE DECREE OF THE KONI OF WEST JAVA PROVINCE NUMBER 084 OF 2021 CONCERNING ENHANCEMENT OF PERSONNEL IN INDRAMAYU REGENCY NATIONAL SPORTS COMMITTEE - Junaedi, Junaedi; Yusuf, Anas; Tahir, Muhammad; Hardi, Rudi (IJBLE Scientific Publications Community Inc., 2023)
The legality of concurrent positions as Deputy Chairperson of the DPRD of Indramayu Regency Based on Koni Decree of West Java Province Number: 084 of 2021 concerning Strengthening the Personnel of the Management of the Indramayu Regency National Sports Committee for the 2021-2025 Service Period. This research was conducted in Indramayu to study and analyze the permissibility of a deputy chairman of the DPRD who is still active and concurrently serving as chairman of the Indonesian National Committee (KONI) at the district level even though this is very much against Article 40 of Law no. 3 of 2005 and the decision of the Constitutional Court No. 27/PUU-V/2007, dated 20 February 2007. Data analysis was performed using qualitative analysis. The findings obtained from this study include: (1). the issuance of the KONI Decree of West Java Province Number: 084 of 2021 concerning the Strengthening of Personnel for the Management of Indramayu Regency for the 2021-2025 service period, namely the Appointment of Deputy Chairperson of the Indramayu Regency DPRD dated 27 May 2021 contrary to Article 40 of Law no. 3 of 2005 concerning the National Sports System (2). the permissibility of a deputy chairman of the DPRD who is still active concurrently serving as chairman of the Indonesian National Committee (KONI) at the district level, even though this is very much against article 40 of Law no. 3 of 2005 and the decision of the Constitutional Court No. 27/PUU-V/2007, February 20 2007, While the West Java Province KONI legalized it and the Regent of Indramayu who understands law and legislation remained silent regarding the issuance of the KONI West Java Province Decree Number: 084 of 2021 concerning Strengthening the Personnel of District Administrators Indramayu Service period 2021-2025, even though this is very much against Article 40 of Law No. 3 of 2005 and the decision of the Constitutional Court No. 27/PUU-V/2007.